Dichelyne (Dichelyne) spinigerus sp. nov. (Nematoda: Cucullanidae) from the marine fish Otolithes ruber (Sciaenidae) off Iran and first description of the male of Philometra otolithi Moravec et Manoharan, 2013 (Nematoda: Philometridae) - Moravec, František; Khosheghbal, Maryam; Pazooki, Jamileh (Acta parasitologica, 2014)
Recent parasitological examinations of the marine perciform fish (tigerteeth croaker) Otolithes ruber (Bloch et Schneider) (Sciaenidae) from off Iran yielded one new and one previously known nematode species: Dichelyne (Dichelyne) spinigerus sp. nov. (Cucullanidae) from the host's intestine in the Persian Gulf and Philometra otolithi Moravec et Manoharan, 2013 (Philometridae) from the ovary in the Persian Gulf and the Sea of Oman. The new species D. spinigerus is mainly characterized by the tail tip of both sexes terminating in two shaply pointed spikes (one dorsal and one ventral) and bearing a pair of minute lateral cuticular spines at its base, situation of both deirids and the excretory pore well posterior to the level of the posterior end of oesophagus, absence of a precloacal sucker and the presence of one or two intestinal caeca. The male and small mature females of the gonad-infecting species P. otolithi are described for the first time, based on light and scanning electron microscopical studies. The male of P. otolithi is most similar to that of P. johnii Moravec et Ali, 2013, but differs from it by the structure of the cephalic end and the number of caudal papillae; both species also differ from each other by the presence of transverse lamellae in the buccal cavity of gravid and subgravid females of P. otolithi, which are missing in those of P. johnii.
Keywords: Dracunculoidea; střeva; Male; Fish Diseases; Iran; vodní organismy; Ascaridida; Microscopy; mužské pohlaví; Spirurida Infections; Animals; Aquatic Organisms; Chordata; ženské pohlaví; mikroskopie; zvířata; nemoci ryb; Ascaridida Infections; Ovary; infekce hlísticemi řádu Spirurida; infekce hlísticemi řádu Ascaridida; Intestines; Írán; Female; ovarium